Analisis Faktor Ibu yang Berhubungan dengan Kejadian Stunting pada Balita di Puskesmas Karanganyar Kabupaten Pekalongan: Analysis of Maternal Factors Associated with the Incidence of Stunting in Toddlers at the Karanganyar Community Health Center, Pekalongan Regency - Isfaizah; Lilin Suryaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2025)
Stunting is a child health problem faced by Indonesia and has an impact on the quality of life of children. The prevalence of stunting in Indonesia in 2022 was 21.6% which was caused by multiple factors. One of the factors that influence stunting is maternal factors, namely age, medical history, nutritional status during pregnancy, and history of exclusive breastfeeding. The purpose of this study was to determine maternal factors related to the incidence of stunting in toddlers at the Karanganyar Health Center, Pekalongan Regency. The research design used correlational analytics with a case-control approach. The study population for the case group was all mothers of stunted toddlers at the Karanganyar Health Center, Pekalongan Regency in January 2025, totaling 44 people. The research sample was mothers of stunted toddlers at the Karanganyar Health Center, Pekalongan Regency in January 2025, totaling 44 people with purposive sampling and a 1:1 ratio, where 44 stunted toddlers and 44 non-stunted toddlers. The research instrument used a questionnaire. Data analysis used frequency distribution and chi square. The results of the study showed that the case group was known to have 77.3% at-risk age, 59.1% non-risk medical history, 79.1% maternal nutrition at risk, 79.1% history of exclusive breastfeeding at risk. The control group was known to have 50% at-risk age, 81.8% non-risk medical history, 77.3% nutritional status at risk, 52.3% history of exclusive breastfeeding at risk. There was a relationship between age (p: 0.015, OR: 3.4), maternal medical history (p: 0.035, OR: 3.1), pregnancy nutritional status (p: 0.000, OR: 28.4), and history of exclusive breastfeeding (p: 0.004, OR: 4.3) with the incidence of stunting at the Karanganyar Health Center, Pekalongan Regency. The incidence of stunting was influenced by age, medical history, pregnancy nutritional status and history of exclusive breastfeeding. It is necessary to increase preventive measures through education about the ideal gestational age, nutritional preparation before pregnancy through education with prospective brides and grooms and the provision of Fe tablets and supervision of taking Fe tablets to prospective brides, carrying out IMD and motivating mothers to provide exclusive breastfeeding. ABSTRAK Stunting merupakan masalah kesehatan anak yang dihadapi Indonesia dan menimbulkan dampak bagi kualitas hidup anak. Prevalensi stunting di Indonesia tahun 2022 sebesar 21,6% yang disebabkan multifaktor. Salah satu faktor yang mempengaruhi stunting adalah faktor ibu yaitu usia, riwayat penyakit, status gizi kehamilan, riwayat pembreian ASI eksklusif. Tujuan penelitian ini adalah mengetahui faktor ibu yang berhubungan dengan kejadian stunting pada balita di Puskesmas Karanganyar Kabupaten Pekalongan. Desain penelitian menggunakan analitik korelasional dengan pendekatan case control. Populasi penelitian untuk kelompok kasus adalah seluruh ibu dari balita stunting di Puskesmas Karanganyar Kabupaten Pekalongan pada bulan Januari 2025 sebanyak 44 orang. Sampel penelitian adalah ibu dari balita stunting di Puskesmas Karanganyar Kabupaten Pekalongan pada bulan Januari 2025 sebanyak 44 orang dengan purposive sampling dan perbandingan 1:1, dimana 44 balita stunting dan 44 balita tidak stunting. Instrumen penelitian menggunakan kuesioner. Analisa data menggunakan distribusi frekuensi dan chi square. Hasil penelitian menunjukkan kelompok kasus diketahui 77,3% usia beresiko, 59,1% riwayat penyakit tidak berisiko, 79,1% gizi ibu berisiko, 79,1% riwayat pemberian ASI eksklusif berisiko. Kelompok kontrol diketahui 50% usia tidak beresiko, 81,8% riwayat penyakit tidak beresiko, 77,3% status gizi tidak beresiko, 52,3% riwayat pemberian ASI eksklusif tidak berisiko. Ada hubungan usia (p: 0,015, OR: 3,4), riwayat penyakit ibu (p: 0,035, OR: 3,1), status gizi kehamilan (p: 0,000, OR: 28,4), dan riwayat pemberian ASI eksklusif (p: 0,004, OR: 4,3) dengan kejadian stunting di Puskesmas Karanganyar Kabupaten Pekalongan. Kejadian stunting dipengaruhi oleh usia, riwayat penyakit, status gizi kehamilan dan riwayat pemberian ASI eksklusif. Perlu meningkatkan langkah-langkah pencegahan melalui edukasi tentang umur kehamilan yang ideal, persiapan gizi sebelum kehamilan melalui edukasi dengan calon pengantin dan pemberian tablet Fe dan pengawasan minum tablet Fe pada calon pengantin, melakukan IMD dan memotivasi ibu untuk memberikan ASI eksklusif.